Pengembangan E-Modul Materi Teks Eksposisi berbasis Flipbook Heyzine untuk Siswa Kelas X SMA Fajrul Islam - Nugraha, Santi; Megawati, Erna; Ikhwati, Azhari (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to 1) develop e-modules using Heyzine Flipbook, 2) describe teacher responses to Heyzine Flipbook e-modules, 3) describe student responses to Heyzine Flipbook e-modules, and 4) find out the effectiveness of using Heyzine Flipbook-based e-modules on exposition text writing skills in grade X of SMA Fajrul Islam. The research method used in this study is the research and development method (Research and Development) ADDIE model with a Quasi-experimental postest only control group design. Data were analyzed using descriptive statistical tests through expert judgment validation for e-modules, normality tests, homogeneity tests, and t tests for e-module effectiveness. The results showed that the e-module Indonesian Heyzine Flipbook-based exposition text material for grade X students of SMA Fajrul Islam is very feasible to be used for learning media with a percentage of material feasibility of 97.5%, language feasibility of 95%, media 82.1%, teacher response of 100%, and student response of 81%. This e-module is also very effective to be used as a learning medium because it shows significant control class postest results and experiments with tcount = 11.9461 > ttable = 2.0042, so is concluded that the e-module developed is very feasible and effective to be used as a learning medium.